2020
DOI: 10.1038/s42004-020-00396-9
|View full text |Cite
|
Sign up to set email alerts
|

Hydrogen release from a single water molecule on Vn+ (3 ≤ n ≤ 30)

Abstract: Water and its interactions with metals are closely bound up with human life, and the reactivity of metal clusters with water is of fundamental importance for the understanding of hydrogen generation. Here a prominent hydrogen evolution reaction (HER) of single water molecule on vanadium clusters Vn+ (3 ≤ n ≤ 30) is observed in the reaction of cationic vanadium clusters with water at room temperature. The combined experimental and theoretical studies reveal that the wagging vibrations of a V-OH group give rise … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

3
23
0
1

Year Published

2021
2021
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 25 publications
(27 citation statements)
references
References 69 publications
(46 reference statements)
3
23
0
1
Order By: Relevance
“…In recent studies on the reaction between water and both cationic and neutral vanadium clusters, Zhang et al. found that three‐atom vanadium clusters, V 3 +/0 , can greatly reduce the energy barrier of the critical step towards effective H 2 release from a single water molecule compared to a single vanadium atom [8g, j] . This finding is consistent with infrared spectroscopic studies under quite similar experimental conditions of V + (H 2 O) n , which indicate that the water molecules on free V + , in particular for n =1, remain intact [12] .…”
Section: Introductionsupporting
confidence: 64%
See 1 more Smart Citation
“…In recent studies on the reaction between water and both cationic and neutral vanadium clusters, Zhang et al. found that three‐atom vanadium clusters, V 3 +/0 , can greatly reduce the energy barrier of the critical step towards effective H 2 release from a single water molecule compared to a single vanadium atom [8g, j] . This finding is consistent with infrared spectroscopic studies under quite similar experimental conditions of V + (H 2 O) n , which indicate that the water molecules on free V + , in particular for n =1, remain intact [12] .…”
Section: Introductionsupporting
confidence: 64%
“…Such a H 2 loss channel is not a priori expected since i) splitting O−H bonds of an isolated water molecule is a very energy demanding process, ii) a single vanadium atom was found to be incapable of inducing H 2 release from a single water molecule due to a high energy barrier, [8g, j] and iii) the already mentioned infrared photodissociation experiments of V + (H 2 O) clusters have not evidenced such a H 2 loss channel [12] . We calculate the energy requirement of this H 2 release process to be 66 kJ mol −1 , which surprisingly is 50 kJ mol −1 lower than that of water loss (116 kJ mol −1 ).…”
Section: Resultsmentioning
confidence: 99%
“…47 Water molecules in collisions with neutral and cationic vanadium clusters V n 0/+ were found by Luo and co-workers to undergo H 2 elimination and formation of V n O 0/+ . 48,49 In the present study, we re-investigate the photochemistry of V + (H 2 O) n , n = 1-4, using a tunable optical-parametric oscillator (OPO) system to extend both wavelength range and resolution and to increase sensitivity due to its high spectral radiation density. We then continue to clusters with up to 41 water molecules to learn more about the electronic and geometric structure in the cluster-size regime where thermally activated hydrogen evolution occurs.…”
Section: Introductionmentioning
confidence: 99%
“…Heteronuclear metal oxide clusters (HMOCs) , can mimic the active sites of industrial multicomponent metal catalysts that are being actively used in the WGS reaction. In the field of gas-phase studies, elementary reactions of CO oxidation ,, and H 2 O reduction have been extensively studied, while a catalytic cycle of WGS has not been established yet. It is extremely challenging to experimentally discover clusters that can abstract the oxygen atom from H 2 O (bond enthalpy: H 2 –O = 5.05 eV) to produce H 2 and then supply the captured oxygen to oxidize CO (bond enthalpy: O–CO = 5.48 eV).…”
mentioning
confidence: 99%